Efficacy of Palm Oil Mill Effluent (POME) in the Improvement and Sustainable Production of Leaf Amaranths (Amaranthus hybridus L) - Adeyemi, F. O. (Journal of Science, Technology and Innovation Research, 2026)
Improved production of leaf vegetables becomes imperative due to their ability to act as supplements in the usual starchy diets of Africans. To make this task achievable, the use of POME is adopted because it is reportedly rich in essential nutrients, and more environmental friendlier than inorganic fertilizers. In this study, five treatments consisting of fresh POME were applied at the rate of 0, 15, 30, 45, 60 t/ha, and NPK 15-15-15 at 400 kg/ha was used for compares. Bed preparation, and other necessary agronomic practices were carried out. There were twenty-four beds of 2 m × 4 m size, arranged in a randomized complete block design field experiment, replicated four times. The treatments were randomly applied to prepared plots, and growth parameters (number of leaves, stem girth, plants height), and total marketable yield (MY) were measured at 5, 6, 7 and 8 weeks after sowing (WAS). Data collected were subjected to analysis of variance (ANOVA) and their means separated, using Duncan Multiple Range Test (DMRT) at 5%. Fresh POME applied at higher rates was significantly effective in improving agronomic parameters and marketable yield of Amaranthus hybridus. Marketable yield, at (t/ha) was in the order: 60 t/ha-8.93>45 t/ha-8.72>NPK-7.50>30 t/ha-5.90>15 t/ha-4.81>Control-2.23. This study concluded that 60 t/ha of fresh POME could be effective in alleviating the challenges encountered in leaf vegetable production, and would reliably act as an alternative to inorganic fertilizers. However, application of POME at 45 t/ha could also be useful where application at 60 t/ha is unattainable.